The U.S. aircraft carrier industrial base : force structure, cost, schedule, and technology issues for CVN 77 - Birkler, J. L., 1944-; United States. Navy.; United States. Department of Defense. Office of the Secretary of Defense; National Defense Research Institute (U.S.) (Santa Monica, CA : Rand, 1998)
This report documents the methods and findings of RAND research on the adequacy of the defense industrial base to support further construction of aircraft carriers and on the cost, schedule, and technology issues associated with building the next carrier, designated CVN 77. If the current carrier force size of 12 ships is to be maintained and if a decay in the quality of basic capabilities is to be avoided, CVN 77 cannot be started more than a year or so beyond the currently planned date of 2002. The earlier CVN is started, the less it will cost. Increasing the build duration from the planned 6.5 years to 8.5 years will also reduce costs. However, timing should not greatly affect the survival of suppliers of carrier components. The report recommends beginning ship fabrication before 2002 (which could save hundreds of millions of dollars); ordering contractor-furnished equipment in advance of shipyard start (a savings of tens of millions); and investment in R & D directed toward adapting production processes and engineering improvements that could reduce the cost of carrier construction, operation and maintenance, and manning. In fact, the costs involved in building and operating carriers are so huge that the Navy should consider establishing a stable annual R & D funding level for these ships. Appendixes to the report provide supporting data.
"Prepared for the United States Navy, Office of the Secretary of Defense."
"National Defense Research Institute."
"MR-948-NAVY/OSD"--Page 4 of cover.
Includes bibliographical references (pages 169-170).
Print version record.
English.
Keywords: Nuclear aircraft carriers -- United States -- Design and construction; Navy-yards and naval stations -- Economic aspects -- United States; Shipbuilding -- United States -- Costs; Shipbuilding industry -- United States; Bases navales -- Aspect économique -- États-Unis.; Construction navale -- États-Unis -- Coût.; Construction navale -- Industrie -- États-Unis.; TECHNOLOGY & ENGINEERING -- Military Science; TECHNOLOGY & ENGINEERING -- Marine & Naval; Navy-yards and naval stations -- Economic aspects; Nuclear aircraft carriers -- Design and construction; Shipbuilding -- Costs; Shipbuilding industry; United States; Naval Science - General; Military & Naval Science; Law, Politics & Government